Dual Antiplatelet Therapy Using Cilostazol With Aspirin or Clopidogrel: Subanalysis of the CSPS.com Trial. Issue 11 (18th August 2021) - Hoshino, Haruhiko; Toyoda, Kazunori; Omae, Katsuhiro; Ishida, Noriyuki; Uchiyama, Shinichiro; Kimura, Kazumi; Sakai, Nobuyuki; Okada, Yasushi; Tanaka, Kortaro; Origasa, Hideki; Naritomi, Hiroaki; Houkin, Kiyohiro; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Although dual antiplatelet therapy (DAPT) with aspirin and clopidogrel reduces the recurrence of ischemic stroke while significantly increasing the bleeding events compared with monotherapy, the CSPS.com trial (Cilostazol Stroke Prevention Study combination) showed that DAPT using cilostazol was more effective without the bleeding risk. In the CSPS.com trial, aspirin or clopidogrel was used as the underlying antiplatelet drug. The effectiveness and safety of each combination were examined and clarified. Methods: In the CSPS.com trial, a multicenter, open-label, randomized controlled study, patients with high-risk, noncardioembolic ischemic stroke 8 to 180 days after onset treated with aspirin or clopidogrel alone at the discretion of the physician in charge were recruited. Patients were randomly assigned to receive either monotherapy or DAPT using cilostazol and followed for 0.5 to 3.5 years. The primary efficacy outcome was first recurrence of ischemic stroke. The safety outcome was severe or life-threatening bleeding. The analysis was based on the underlying antiplatelet agents. Results: A total of 763 patients taking aspirin and 1116 taking clopidogrel were included in the intention-to-treat analysis. Although the clopidogrel group had more risk factors than the aspirin group, the primary efficacy outcome and safety outcome did not differ significantly between the 2 groups. In the aspirin group, the primary efficacy outcome and safety outcome did not differ significantly between the DAPT group and the aspirin-monotherapy group. In the clopidogrel group, the primary end point occurred at a rate of 2.31 per 100 patient-years in the DAPT group and 5.19 per 100 patient-years in the clopidogrel-monotherapy group (hazard ratio, 0.447 [95% CI, 0.258–0.774]). Safety outcome did not differ significantly between groups (0.51 per 100 patient-years versus 0.71 per 100 patient-years, respectively; hazard ratio, 0.730 [95% CI, 0.206–2.588]). Conclusions: The combination of cilostazol and clopidogrel significantly reduced the recurrence of ischemic stroke without increasing the bleeding risk in noncardioembolic, high-risk patients. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01995370. URL: https://www.umin.ac.jp/ctr/ ; Unique identifier: UMIN000012180.